The Influence of Work Environment and Competency on Organizational Commitment Through Self-Efficacy - Ikmal Anis Makhshusho (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is to determine the relationship between the influence of the Work Environment, Competence, Self-Efficacy on Organizational Commitment at the UPPD I Transportation Service. The analytical method used in this study is the Structural Equation Model (SEM) and using Partial Least Square (PLS). The sample method used is Probability Sampling and uses a saturated sample technique of 120 respondents who are Employees at the UPPD I Transportation Service. The results show that Work Environment and Competence have a positive effect on Organizational Commitment, Work Environment and Competence have a positive effect on Organizational Commitment through Self-Efficacy